Estrogen predicts multimodal emotion recognition accuracy across the menstrual cycle - Jang, Daisung; Lybeck, Max; Cortes, Diana Sanchez; Elfenbein, Hillary Anger; Laukka, Petri (PLOS ONE, 2024)
Researchers have proposed that variation in sex hormones across the menstrual cycle modulate the ability to recognize emotions in others. Existing research suggests that accuracy is higher during the follicular phase and ovulation compared to the luteal phase, but findings are inconsistent. Using a repeated measures design with a sample of healthy naturally cycling women (N = 63), we investigated whether emotion recognition accuracy varied between the follicular and luteal phases, and whether accuracy related to levels of estrogen (estradiol) and progesterone. Two tasks assessed recognition of a range of positive and negative emotions via brief video recordings presented in visual, auditory, and multimodal blocks, and non-linguistic vocalizations (e.g., laughter, sobs, and sighs). Multilevel models did not show differences in emotion recognition between cycle phases. However, coefficients for estrogen were significant for both emotion recognition tasks. Higher within-person levels of estrogen predicted lower accuracy, whereas higher between-person estrogen levels predicted greater accuracy. This suggests that in general having higher estrogen levels increases accuracy, but that higher-than-usual estrogen at a given time decreases it. Within-person estrogen further interacted with cycle phase for both tasks and showed a quadratic relationship with accuracy for the multimodal task. In particular, women with higher levels of estrogen were more accurate in the follicular phase and middle of the menstrual cycle. We propose that the differing role of within- and between-person hormone levels could explain some of the inconsistency in previous findings.